When is a two-stage single-arm trial efficient? An evaluation of the impact of outcome delay. (May 2022) - Mukherjee, Aritra; Wason, James M.S.; Grayling, Michael J.
Abstract: Background: Simon's two-stage design is a widely used adaptive design, particularly in phase II oncology trials due to its simplicity and efficiency. However, its efficiency can be adversely affected when the primary end-point takes time to observe, as is common in practice. Methods: We propose an optimal design, taking the delay in observing treatment outcome into consideration and compare the efficiency gained from using Simon's design over a single-stage design for real-life oncology trials. Based on the results, we provide a general rule-of-thumb for determining whether a two-stage single-arm design can provide any added advantage over a single-stage design, given the recruitment rate and primary end-point length. Results: We observed an average 15–30% loss in the estimated efficiency gain in real oncology trials that used Simon's design due to the delay in observing the treatment outcome. The delay-optimal design provides some advantage over Simon's design in terms of reduced sample size when the delay is large compared to the recruitment length. Discussion: Simon's two-stage design provides large benefit over a single-stage design, in terms of reduced sample size, when the primary end-point length is no more than 10% of the total recruitment time. It provides no efficiency advantage when this ratio is above 50%. Highlights: The delay in observing treatment outcome reduces the efficiency of an adaptive trial. Oncology trials using Simon's design lost 15–30% efficiency on average due to delay. A delay-optimal design helps to overcome these issues if the delay is moderate. Simon's design maximises gain if delay is less than 10% of total recruitment time. Simon's design is inefficient when delay is more than 50% of total recruitment time.